Pollen gathering by honey bees in La Crosse County, Wisconsin - Severson, David William (My University, 1978)
Pollen was trapped from honeybee (Puis mellifera L.) colonies using the O.A.C. pollen trap at six randomly selected sites, one of which was a commercial apple orchard, within LaCrosse County, Wisconsin during the 1977 blooming season. The corbicular pellets were generally unifloral, which allowed for a separation of the pollen species on a color basis. Once sorted by color, each subsample was weighed to determine the relative percent utilization of each species at each site. Slides, used for species identification, were made of each color using the acetolysis technique. Reference slides from known plant species were made and compared to verify the identities of the bee-gathered pollens. A study of the major pollen sources within the county revealed that these sources are quite varied throughout the blooming season. Some of the more dominant and long-blooming species were oak, dandelion, fruit trees, clovers, sumac, corn, buckwheat, and composites. Other species such as boxelder, ash, raspberry, and red-osier dogwood are utilized for large amounts of pollen, but have relatively short blooming periods. The pollen season can be divided into three distinct categories; the early April to late May tree sources, the late May to mid-June shrubs, and the herbaceous species from mid-June through September. A considerable amount of the pollen collected came from supposedly wind-pollinated species, raising some question as to the true nature of pollination vector and flower-form relationships. The bees appear to be inclined to forage from any floral source in the apiary vicinity that offers adequate amounts of pollen. A study of differences in major pollen sources in different apiaries, revealed that the same basic species were utilized at all areas sampled. There were, however, significant differences in the amounts of pollen collected from these species. A noticeable exception was buckwheat, which is not routinely in cultivation throughout the county and as such, was only foraged for pollen in apiaries within flight range of this crop. A study of plants competitive to commercial apple pollination determined that commercial pollination efforts can be severely affected by competitive plants growing in the orchard vicinity. The bulk of the competition was supplied by oak and dandelion.
Keywords: Bees -- Wisconsin -- La Crosse County; Pollen